Evaluation of some nitrobenzimidazoles effects on germination parameters of various wheat species - KÜLEN, Seda (Journal of Agricultural Sciences (Belgrade), 2024)
The aim of this study is to investigate the effect of some benzimidazole derivatives on the germination parameters of bread and durum wheat varieties. These derivatives contain both non-substitute and substitute benzimidazole structures to determine the effect of substituents on germination. Three different durum wheat varieties (Çeşit-1252, Eminbey, and Kızıltan-91) and three different bread wheat varieties (Demir 2000, Bayraktar 2000, and Tosunbey) were used in the study. Germination rates, coleoptile lengths, and root lengths of wheat varieties were measured by using 10-6 M solutions of benzimidazole derivatives on the 8thgermination day. The obtained results demonstrated that the efficiency of the benzimidazole compounds varies depending on the wheat varieties and germination parameters. 5-nitro-1H-benzimidazole-6-amine (6) had the highest effect on germination rate while 1H-benzimidazole (1) had the highest effect on root and coleoptile lengths in all varieties.